Bird breeding data for Wytham Woods, Oxfordshire, UK, 2020 and 2021 - Beck, K; Firth, J A; McMahon, K; Croft, Sam; Cole, E F; Sheldon, B (NERC EDS Environmental Information Data Centre, 2022)
This dataset contains information on the following: nest building, identity of breeding pairs, date when the first egg is laid, number of eggs, hatch date and the number and condition of fledglings for great tits, blue tits, marsh tits and coal tits. The data presented were collected in Wytham Woods, Oxfordshire, UK during April and June in 2020 and 2021 by Keith McMahon, Sam Croft and Kristina Beck, as part of a long-term nestbox project on the breeding biology of birds. The work was supported by the Natural Environment Research Council (Grant NE/S010335/1), The ecology of behavioural contagion in natural systems.